Antioxidant activity of Sind sardine hydrolysates with pistachio green hull (PGH) extracts. (February 2019) - Sarteshnizi, Roghayeh Amini; Sahari, Mohammad Ali; Gavlighi, Hassan Ahmadi; Regenstein, Joe M.; Nikoo, Mehdi
Abstract: High rates of oxidation during hydrolysis are one the main problems with hydrolysate production from fatty fishes such as Sind sardines. The purpose of this study was to control oxidation by different pretreatments with pistachio green hull (PGH) extracts as an antioxidant. Different enzyme levels (1.3%, 2.5%, and 5%), pretreatments of fish mince (washing, defatting, fish protein isolate (FPI)), and the addition of PGH as well as nitrogen gas treatment were studied on lipid oxidation during hydrolysis of Sind sardines ( Sardinella sindensis ). The antioxidant properties of the hydrolysates were also studied. Results for thiobarbituric acid reactive substances indicated that the nitrogen gas and 5% (w/w) enzymatic treatment significantly decreased lipid oxidation along with having a higher degree of hydrolysis and higher antioxidant activity for the hydrolysate. FPI was more effective than washing in controlling oxidation while defatting using isopropanol was the most effective. PGH (260 µg/ml) effectively controlled the oxidation of mince and washed mince ( P  < 0.05) but it was not effective for FPI as seen by the higher oxidation of heme-pigments and weaker metal chelating activity of PGH. Interaction of hydrolysates from all treatments and PGH showed significant combined DPPH radical scavenging and metal chelating activity ( P  < 0.05). Therefore, defatting using isopropanol and addition of an antioxidant such as PGH can effectively be used for inhibition of lipid oxidation during hydrolysis and improvement of antioxidant activity of hydrolysates. Graphical abstract: Highlights: Increased dosage of enzyme to 5% can control lipid oxidation during hydrolysis. Pretreated mince with isopropanol was the most effective to control oxidation. Interaction of hydrolysates-PGH showed higher antioxidant activity than hydrolysate.